PREVALENSI OBSTRUCTIVE SLEEP APNEA DENGAN KUESIONER STOPBANG DAN RISIKO STROKE PADA POPULASI NORMAL - Pricilla Yani Gunawan, Salim Harris, Fitri Octaviana, Herqutanto (NEURONA, 2013)
INTRODUCTION STROKE IS THE SECOND LEADING CAUSE OF DEATH AND THE MOST DISABLING DISEASE IN THE WORLD INCLUDING INDONESIA OBSTRUCTIVE SLEEP APNEA OSA IS ONE OF THE RECENT KNOWN STROKE RISK FACTOR AND STOPBANG QUESTIONNAIRE WAS BELIEVED TO BE ONE OF THE BEST SCREENING TOOL